Selenium Sources Affect Protein Concentration, Thioredoxin Reductase Activity and Selected Production Parameters in Reovirus Infected Broiler Chickens - Burgos, Sigfrido; Edens, F.; Read-Snyder, J.; Cantor, A.; Burgos, Sergio A. (International Journal of Poultry Science, 2006)
Successful Avian Reovirus (ARV) infections ultimately result in decreased weight gains coupled with increased mortality. Selenium (Se) is a structural component of Thioredoxin Reductase (TRX), an enzyme capable of quenching intracellular free radicals and influencing redox balance. The aim of this study was to determine the various effects that Se-containing diets fed to ARV-infected broilers had on protein concentrations, TRX activity, body weights and mortality. Eggs were obtained from Cobb breeders that had been maintained on isocaloric Torula yeast diets containing either no supplemental Se, sodium selenite at 0.3 ppm, or organic Se (Sel-Plex®, Alltech, Inc., Nicholasville, KY) at 0.3 ppm. Chicks hatched from those eggs were placed on Torula yeast broiler diets containing 1) no supplemental Se, 2) 0.3 ppm sodium selenite, or 3) 0.3 ppm organic Se similar to their respective parents` diets. On day of hatch, 60 chicks per dietary Se treatment were placed into either Control or Virus-infected groups in heated-growing batteries in separate isolation rooms. Chicks in the Virus-infected groups were given each an oral gavage of 0.5 ml of ARV-CU98 (104.2 pfu/ml/chick), and Control chicks were given the medium only. At 14 and 21 days of age, the birds were weighed, bled, killed by CO2 asphyxiation, and tissues collected for analyses. Data from this 2 X 3 factorially arranged, completely randomized experimental design were analyzed using the GLM procedure of SAS. ARV-infected birds had significantly lower average body weights (ABW) at 14 and 21 days (P< 0.0001), three times higher mortality rates, and decreased tissue protein concentration (p< 0.001) than controls. Se treatments did not affect ABW and mortality, but did significantly improve plasma protein concentration (p< 0.05) and TRX activity in both, healthy and virus-challenged bird. Our findings suggest that ARV infection depresses growth, increases mortality and reduces protein concentration in various tissues, whereas Se is beneficial against ARV infection in broilers through an improved antioxidant status.